Rewriting the horror genre through new digital realities in Cam by Daniel Goldhaber - Bedoya Forno, Rodrigo (2020)
This article seeks to explain how the film Cam works with some themes of the horror genre (the doppelgänger, or double, in particular) to show how the new digital technologies have change the dynamics of our everyday life. The film offers, based in the story of a cam girl whose identity is taken by an unknown entity, a look on how digital technologies have become work and provision tools, creating a new life dynamic in which we don´t need to shift and everything can be done with a click. The film also exposes the new forms of the horror genre, showing Internet as a place where violence and sex have become tools to generate interactivity with users, and allowing better profits. But Cam also works with some contemporary fears that come with the new technologies (to be blocked from an account, the possibility of being hacked) to create a universe where all explanations are possible, and where it´s very hard to establish which is the enemy to beat.